2011
DOI: 10.1016/j.physbeh.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of palatable food decreases the anorectic effects of serotonergic, but not dopaminergic drugs in baboons

Abstract: We examined the effects of periodic access to a palatable, high sugar content food (candy) in 8 male baboons on the anorectic response to d-amphetamine, which increases dopamine, and dexfenfluramine, which increases serotonin. During candy access, up to 200 candies containing 75% of energy as sugar were available during the morning on Mondays, Wednesdays and Fridays; food pellets (19% of energy as sugar) were available in the afternoon and throughout the remaining days of the week. During candy access, baboons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Since previous studies have shown a lack of interaction between the anorectic properties of amphetamine and diet palatability / energy density (Wellman et al 1982), we hypothesize that the long-term exposure to the high-fat diet may have induced neuroadaptations in the dopaminergic system, which were responsible for the sensitized anorectic effect to D-amphetamine observed here. In support of this hypothesis are previous reports that repeated access to candies in baboons increases their sensitivity to the effects of D-amphetamine on the intake of both candies and regular food (Foltin 2011). …”
Section: Discussionsupporting
confidence: 64%
“…Since previous studies have shown a lack of interaction between the anorectic properties of amphetamine and diet palatability / energy density (Wellman et al 1982), we hypothesize that the long-term exposure to the high-fat diet may have induced neuroadaptations in the dopaminergic system, which were responsible for the sensitized anorectic effect to D-amphetamine observed here. In support of this hypothesis are previous reports that repeated access to candies in baboons increases their sensitivity to the effects of D-amphetamine on the intake of both candies and regular food (Foltin 2011). …”
Section: Discussionsupporting
confidence: 64%
“…The increased expression of the 5‐HT 2C receptors after a hypercaloric diet is noteworthy because in our experimental model this type of diet produced different effects from those described in the literature. Classically, hypercaloric diets increase the proliferation of hypothalamic neurons that produce orexigenic peptides (Bouret et al, 2008) and reduce the anorexigenic effects of serotonergic drugs (Foltin, 2011). Moreover, diets rich in sugars and lipids can alter hypothalamic homeostatic control, increasing hunger signals and blocking satiety signals (Erlanson‐Albertsson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We examined the effects of consumption of a high-sucrose food on the anorexigenic actions of amphetamine, dexfenfluramine, heroin, and naloxone by determining complete dose–response functions before, during, and after a period of access to Skittles candy in eight experimentally-naive male baboons (Foltin, 2011). Baboons were administered with a test dose of drug or placebo on Tuesday and Thursday of each week.…”
Section: Effect Of Sucrose Consumption On Sensitivity To Drug Effectsmentioning
confidence: 99%
“…This finding parallels the work of Morgan et al (2002) according to which submissive male cynomolgus monkeys self-administered more intravenous cocaine compared with dominant monkeys. On the basis of these findings, we examined the effect of social status (assigned by three independent observers) on Skittle consumption and response to pharmacological agents in the group of eight male baboons that were studied in the investigation by Foltin (2011). Although not significantly different, the four submissive male baboons consumed on average 18% more candy than the four dominant baboons.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation